Autonomic nervous system activity and performance in competitive swimming: A field study - Garet, M.; Pichot, V.; Tournaire, N.; Roche, F.; Duverney, D.; Barthelemy, J. C. (3rd FEPS Meeting, Nice, 28 June - 2 July 2003, 2003)
The aim of this study was to assess the potential use of heart rate variability (HRV) analysis, a sympathovagal indice, as a biomarker in the control of the effect of physical training loads on performance at an individual level as it has already been demonstrated in groups of elite sportsmen. Seven regional-level swimmers (4 male, 3 female; 16.6±0.5 years; 169.3±5.9cm, 59.3±6.3kg, Tanner stages: S4) with a history of 6.4±0.9 years of practice, swimming 9 hours per week during the ongoing season. Maximal aerobic power performance (400-m freestyle) was performed before (P1), and after 3 weeks of intensive training (P2) and 2 weeks of tapering (P3). HRV (time and frequency domain) was recorded during the night before each performance as well as twice a week along the training program. Weekly training loads were individually quantified (sum of daily mileage*intensity*perceived exertion) and heart rate, perceived exertion, stroke rate and distance per stroke were monitored on each performance assessment. Data were compared using a two factors ANOVA, weeks and subjects for group analysis. Mean and individual training loads along with perceived exertion increased from wk1 to wk3 and decreased to wk5 (P=0.018 to <0.0001). Global HRV and parasympathetic indices evolved individually, decreasing from wk1 to wk3 and increasing to wk5 in 5 swimmers, while they continuously decreased or increased in 2. All performances were maximal. Best and worst performances were respectively realized when global and parasympathetic indices of HRV were highest (P3 in 5 swimmers and P1 in 2), and lowest (P2 in 6 and P3 in 1). Excepted in 1 swimmer, the higher total power spectrum, pNN50 and RMSSD indices of HRV were, the better the performance. Thus, HRV evolution is highly individual in response to training loads and is a powerful predictor of physical performance, a high global and parasympathetic activity being required for better performance achievement.